Structure and Functions of Human Serum Albumin in Normal Conditions and in Patients with Liver Cirrhosis - A. A. Turkina; M. V. Mayevskaya; M. S. Zharkova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim: to highlight the main points of albumin synthesis, posttranslational modifications and functions in normal conditions and in patients with liver cirrhosis.Key points. Albumin is the most abundant protein in blood plasma. Along with oncotic properties, albumin performs transport, antioxidant, immunomodulatory and endothelioprotective functions. Serum albumin in patient with liver cirrhosis undergoes modifications, leading to functional impairment. Human serum albumin is a compaund of human mercaptalbumin with cysteine residues having a reducing ability, and oxidized human non-mercaptalbumin. The proportion of irreversibly oxidized non-mercaptalbumin-2 with impaired functional activity increases in liver cirrhosis.Conclusion. The conformational structure of the albumin molecule plays an important role in maintaining its non-oncotic functions. Non-oncotic functions depend on albumin conformation. Further investigation of albumin conformation and albumin functions in patients with hepatic insufficiency can serve as an additional criterion for assessing the severity of cirrhosis and predictor of complications may become an additional criterion to new clinical applications and treatment strategies of liver failure.